Implementasi Program Vaksinasi Covid 19 di Puskesmas Kecamatan Sirah Pulau Padang Kabupaten Ogan Komering Ilir - Haryanto, Sandi; Kencana, Novia; Kariem, M Qur’anul (Jurnal Publisitas, 2023)
The Covid 19 Vaccine Program found several efforts by the Indonesian government to solve the Covid-19 problem. The Covid-19 vaccination aims to create immunity so that people become healthier in carrying out their daily activities. When the vaccine has been injected, the vaccine triggers antibodies to recognize and recognize the attenuated virus. Then the body will kill the virus and reduce the risk of exposure, the theory used is the theory of Edward III. The purpose of this study was to find out how to implement the Covid 19 Vaccination program at the Sirah Pulau Padang District Health Center, Ogan Komering Ilir Regency. In this writer's thesis qualitative research methods start from the data collection methods used are observation, interviews and documentation, descriptive data analysis methods with data reduction stages, data exposure, and conclusions. The results showed that the implementation of the Covid 19 Vaccination Program at the Sirah Pulau Padang District Health Center, Ogan Komering Ilir Regency was declared successful because it had achieved the Covid 19 Vaccination target which had been targeted by the Sirah Pulau Padang District Health Center.